Macrophage Migration Inhibitory Factor Deficiency Causes Prolonged Hearing Loss After Acoustic Overstimulation. Issue 6 (July 2015) - Kariya, Shin; Okano, Mitsuhiro; Maeda, Yukihide; Hirai, Haruka; Higaki, Takaya; Noyama, Yasuyuki; Haruna, Takenori; Nishihira, Jun; Nishizaki, Kazunori
<x xml:space="preserve">Abstract</x> Hypothesis Macrophage migration inhibitory factor plays an important role in noise-induced hearing loss. Background Macrophage migration inhibitory factor is an essential factor in axis formation and neural development. Macrophage migration inhibitory factor is expressed in the inner ear, but its function remains to be elucidated. Methods Macrophage migration inhibitory factor-deficient mice (MIF−/− mice) were used in this study. Wild-type and MIF−/− mice received noise exposure composed of octave band noise. Auditory brainstem response thresholds were examined before (control) and at 0, 12, and 24 hours and 2 weeks after the intense noise exposure. Morphological findings of cochlear hair cells were investigated using scanning electron microscopy. Histopathological examination with hematoxylin and eosin staining and TUNEL assay were also performed. Results In both the wild-type and MIF−/− mice, acoustic overstimulation induced significant hearing loss compared with the control level. Two weeks after the intense noise exposure, the MIF−/− mice had an increased hearing threshold compared with the wild-type mice. Scanning electron microscopy demonstrated that the outer hair cells in the MIF−/− mice were affected 2 weeks after noise exposure compared with the wild-type mice. TUNEL-positive cells were identified in the organ of Corti of the MIF−/− mice. Conclusion The MIF−/− mice had prolonged hearing loss and significant loss of cochlear hair cells after intense noise exposure. Macrophage migration inhibitory factor may play an important role in recovery from acoustic trauma. Management of macrophage migration inhibitory factor may be a novel therapeutic option for noise-induced hearing loss.